PENDEKATAN KONSEP TA’AWUN DALAM SIYAR TERHADAP KONFLIK TUMPANG TINDIH KEDAULATAN WILAYAH UDARA DAN FLIGHT INFORMATION REGION: ALTERNATIF PENYELESAIAN KASUS TUMPANG TINDIH WILYAH UDARA INDONESIA DAN FLIGHT INFORMATION REGION SINGAPURA - Achmad Andaru, Djarot Dimas (Journal of Islamic Law Studies, 2021)
Islamic law as a law that applies universally, has governed relations between people and between state institutions that cross national borders. One of the principles of international law or Siyar in Islam is the principle of ta'awun, which is a principle of cooperation or help between countries to achieve common good. Conflicts of interest in overlapping air sovereignty territories and the Flight Information Region between Indonesia and Singapore are one example of the disharmony of the practice of modern international cooperation in the management of air and air navigation safety, which is based on an instrument of international cooperation. The concept of state sovereignty in modern international law is proven to put forward the ego of the interests of each country which is contrary to the objectives of international law itself. The approach of Islam to international law offers a different perspective on how proper international relations between countries should be carried out.